Indifferentiating the Undifferentiated in Kristeva’s Revolution in Poetic Language - Watkin, William (Acta Nova Humanistica: A Journal of Humanities Published by New Bulgarian University, 2024)
When Kristeva published her doctoral thesis La révolution du langage poétique in the early 1970s, its engagement with the philosophy of difference was groundbreaking. However, nearly fifty years later, the rise of indifferential systems of thought in continental philosophy, such as we find in Giorgio Agamben’s archeology, Alain Badiou’s ontology, set theory, and analytic extensionalism, means that, returning to Kristeva’s foundational text, it can appear dated and impossible to recuperate for a twenty-first century philosophical situation. Yet central to Kristeva’s work is the semiotic chora, which is described as uncertain, indeterminate, quantity without quality, suspensive, nonexpressive and undifferentiated. While, intrinsic to her theorization of the thetic as central to the symbolic order is Frege’s extensional, indifferent theory of denotation and the indifference of truth. Both the semiotic and the thetic suggest that Kristeva is not insensible to the conceptual potential of the philosophy of indifference. Taking the semiotic chora and the positing function of the thetic as our starting point, therefore, this paper will attempt a remapping of Kristeva’s work by thinking of the chora, and the thetic indifferentially.